The Influence of Village Fund on the Job Market and Economic Growth in Dairi Regency - Malau, Albert Gamot; Hotman, Jah (International Journal of Membrane Science and Technology, 2023)
One of the problems in Indonesia is the imbalance in development between cities and villages. The government makes efforts to increase village development by providing village fund assistance. One of the Village Fund Recipients is Dairi Regency. Village fund receipts in 2015 had a positive influence, where the number of poor people decreased by 1.6%, but in 2016 people experiencing poverty increased by 0.16%. From these problems, this research aims to analyze the influence of village funds on unemployment rate, labour force, poor population, and gross regional domestic product of Dairi Regency last year, (2) to analyze the influence of village funds on the Human Development Index of Dairi Regency, Total Employed, undergraduate education level, and last year’s village funds. Economic Development is one of the goals of a country/region to increase the availability or expand the distribution of goods’ basic needs for life, clothing, housing, education, and health. The method used was quantitative with a model of Two Stage Least Square (2SLS) using the SAS program version 9.2 in 2010-2022. The results show that village funds, labour force, and gross regional domestic product of Dairi Regency last year had a real and significant effect of 95%. Variables of village funds are very responsive (elastic), affecting the gross regional domestic product of Dairi Regency in the long term. Variables of village funds are influenced by village income, education level, Human Development Index, and last year’s Village Funds. Last year’s village income and village fund variables had a real and significant effect of 95%. Village income variables are very responsive to influencing village funds in Dairi Regency in the short term and the long term.